1, 001 Subclavian Perivascular Brachial Plexus Blocks: Success With a Nerve Stimulator. Issue 1 (1st January 2000) - Franco, Carlo D.; Vieira, Zairo E.G.
Abstract : Background and Objectives: Among the supraclavicular approaches to the brachial plexus, the subclavian perivascular technique is a well-established method of anesthesia of the upper extremity. Ever since Kulenkampf described his technique, eliciting a paresthesia has been almost mandatory ("no paresthesia, no anesthesia"). Lately, nerve stimulators have become more popular. However, up to the present time, clinical studies involving the nerve stimulator have failed to show success rates comparable to paresthesia techniques. Methods: Data from 1, 001 consecutive, subclavian perivascular blocks were prospectively gathered over 2.5 years. All blocks were performed according to Winnie's technique, but using a nerve stimulator instead of a paresthesia. When an adequate response was obtained, 35 to 40 mL of local anesthetic solution was injected. Results: Nine hundred seventy-three blocks (97.2%) were completely successful; 16 blocks (1.6%) were incomplete and needed supplementation; and 12 blocks (1.2%) failed and required general anesthesia, giving a success rate for regional anesthesia of 98.8%. Conclusions: The subclavian perivascular block consistently provides an effective block for surgery on the upper extremity. At the site of injection with this technique, the plexus is reduced to its smallest components and the sheath is reduced to its smallest volume, which explains in great part the success obtained with this block. We believe that we have demonstrated a nerve stimulator technique that is both highly successful and safe; no clinical pneumothorax was found nor did any other major complications develop.